Osteoporose e doença periodontal em mulheres pós-menopausadas - Passos, Johelle de Santana (2007)
Osteoporosis represents a serious problem of public health that reaches frequently the postmenopausal women. The clinical importance of systemic bone loss as a contributory factor towards alveolar bone loss and subsequent loss of teeth still merits further study, given that osteoporosis and periodontal disease lead to significantly increased morbidity and mortality, and also higher public expenditure. This case-control study had the aim of evaluating the association between osteoporosis and PD in postmenopausal women, aged 50 and over, invited on CEPARH-Feira de Santana-BA to oral exam and dental treatment at Diagnostic Oral I Subject Clinic from State University of Feira de Santana-BA. The sample consisted of 139 postmenopausal women, being 48 of the case group (women with periodontal disease) and 91 of the control group (women without periodontal disease). The diagnosis of periodontal disease was established after oral clinic exam utilizing as descriptors the measurements of probing depths of sulcus/pockets, recession/hyperplasia, clinic attachment level, index of plaque, bleeding on probing and gingival, being confirmed by panoramic radiographic exam with bone resorption evaluation. The diagnosis of osteoporosis was made by investigating densitometry reports obtained previously. After systematization of colleted data, descriptive analysis of the variables, stratified analysis, and multivariate analysis using logistic regression were applied. Comparisons of proportions were performed using the Chi-square and Fisher test. Crude odds ratios (OR) and adjusted for confounders and controlled for effects modifiers were calculated with significance level at 5%. The results showed a principal association crude OR of 2.58 (95%IC: [1.01-6.82]), while on model controlled for schooling and adjusted for smoking habits and age, the OR was 6.70 (95%IC: [1.34-41.66]). The findings showed a statistically significant association between osteoporosis and PD, indicating that postmenopausal women with osteoporosis and low schooling levels have a greater chance of having PD than do those without osteoporosis.